Kinematics Analysis and Experiment of a Cockroach-Like Robot - 高勇 陈伟海 陆震 (Shanghai jiao tong da xue xue bao, 2011)
This article describes the structure of the cockroach-like robot.Both kinematics and locomotion control are inspired by biological observations in cockroaches.Based on cockroach-like robot kinematics analysis,screw theory,and the production-of-exponential （POE） formula,this paper focuses on the inverse kinematics which uses Paden-Kahan sub-problems to obtain directly the displacement of joint angles.The forward kinematics derives the relationship between joint angles according to the natural restrictions.Then,by using the POE formula,it can deduce the body pose and realize online trajectory control and planning.Through simulation and experimentation,it is proved that the straight-line walking and turning gait algorithms have static stability and the inverse kinematics analysis of cockroach-like robot is correct.